Preoperative Sleep Disturbance Exaggerates Surgery-Induced Neuroinflammation and Neuronal Damage in Aged Mice - Pengfei Ni; Hongquan Dong; Qin Zhou; Yiwei Wang; Menghan Sun; Yanning Qian; Jie Sun (Mediators of Inflammation)
Postoperative cognitive dysfunction (POCD) is defined as new cognitive impairment (memory impairment and impaired performance) after surgery, especially in aged patients. Sleep disturbance is a common phenomenon before surgery that has been increasingly thought to affect patient recovery. However, little is known about the functional impact of preoperative sleep disturbance on POCD. Here, we showed that tibial fracture surgery induced cognitive deficit and production of proinflammatory cytokines interleukin-6 (IL-6) and IL-1β, along with microglia and astrocyte activation, neuronal damage, and blood-brain barrier (BBB) disruption. Preoperative sleep disturbance enhanced the surgery-induced neuroinflammation, neuronal damage, BBB disruption, and memory impairment 24 h after surgery. Taken together, these results demonstrated that preoperative sleep disturbance aggravated postoperative cognitive function in aged mice and the mechanism may be related to central nervous system (CNS) inflammation and neuronal damage.